Gambaran Pengetahuan, Sikap dan Perilaku Kelompok Aisyiyah Tentang Penggunaan dan Waktu Simpan Sediaan Farmasi Steril di PCA Kecamatan Purwokerto Timur: Overview of Knowledge, Attitudes, and Behavior of the Aisyiyah Group Regarding the Use and Shelf Life of Sterile Pharmaceutical Preparations in the PCA of East Purwokerto District - Erza Genatrika; Elza Sundhani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Sterile pharmaceutical preparations such as eye drops, nose drops, and ear drops have specific uses and shelf lives. Currently, based on the information obtained, the community, especially members of Aisyiyah PCA Purwokerto Timur, can easily obtain these sterile pharmaceutical preparations. The community's ignorance in using and storing these preparations can endanger their health. This community service activity aims to describe the knowledge, attitudes, and behavior of the Aisyiyah group regarding the use and shelf life of sterile pharmaceutical preparations in PCA Purwokerto Timur before and after training. The study uses a cross-sectional design with a quantitative approach. The number of respondents used is the total population attending the training. Of the 35 training participants, 20 (57.1%) had good knowledge, attitudes, and behavior before the training, and 15 (42.9%) had fairly good knowledge, attitudes, and behavior. Furthermore, after the training, 35 (100%) had good knowledge, attitudes, and behavior regarding the use and shelf life of sterile pharmaceutical preparations. Knowledge can influence the attitudes and behavior of Aisyiyah PCA Purwokerto Timur members regarding the use and shelf life of sterile pharmaceutical preparations.